2019
DOI: 10.7567/1882-0786/aaf469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation on proliferation and bone-formation by osteoblast-like cells cultured on carbon nanowalls scaffolds

Abstract: Carbon nanowalls (CNWs) were synthesized by radical injection plasma-enhanced chemical vapor deposition and used as scaffolds for cell culture. The proliferation of osteoblast-like cells (Saos-2) was enhanced on the CNW scaffold upon electrical stimulation (ES) with 10 Hz square pulses at a current of 226 nA. However, after incubation with ES for 10 d, differentiation of the cells toward bone formation was suppressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…1−8 We recently reported that CNWs are useful as a cell culture scaffold. 8 Scaffolds aid cell proliferation, differentiation, and morphological control. For culturing cells, micro-or nanostructures have been used.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1−8 We recently reported that CNWs are useful as a cell culture scaffold. 8 Scaffolds aid cell proliferation, differentiation, and morphological control. For culturing cells, micro-or nanostructures have been used.…”
mentioning
confidence: 99%
“…The ES was 226-nA-current pulses at a repetition of 10 pulses/s. 8 By the cell culture on a CNW scaffold, extracellular calcium content was an indicator of the differentiation of osteoblast cells and was lower and exposed to ES compared to when cells were grown on polystyrene (PS). 8 Moreover, cell morphology was different: the cells aggregated on the CNW scaffold following ES, whereas no aggregation was observed when the cells were grown on PS.…”
mentioning
confidence: 99%
See 3 more Smart Citations